2019
DOI: 10.1016/j.jds.2019.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bifid mandibular canal according to gender, type and side

Abstract: Background/purpose An awareness of mandibular canal variations may help prevent complications due to nerve damage that can occur during surgery. The aim of this study is to evaluate the variations of mandibular canal distribution and frequency via cone beam computed tomography (CBCT), retrospectively, in a Turkish population. Materials and methods The study population comprises 500 (250 female, 250 male) randomly selected participants between the ages of 14 and 79 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 29 publications
2
35
0
2
Order By: Relevance
“…CT and CBCT have been used to overcome the limitations of panoramic radiography (Fukami et al, ). So far, four studies have used both panoramic and CBCT (López‐Videla et al, ; Moro et al, ; Muinelo‐Lorenzo et al, ; Neves et al, ), two have used a combination of CT and CBCT (Rouas, Delbos, & Nancy, ; Shen et al, ), 21 have used only CBCT, one of them determining the prevalence of BMC in children (Afsa & Rahmati, ; Borgonovo et al, ; de Castro et al, ; de Oliveira‐Santos et al, ; Kang et al, ; Kuribayashi et al, ; Li et al, ; Luangchana et al, ; Naitoh et al, ; Neves et al, ; Ogawa et al, ; Okumu & Dumlu, ; Orhan et al, ; Orhan et al, ; Rashsuren et al, ; Shah et al, ; Sonneveld et al, ; Villa et al, ; Yang et al, ; Yi et al, ; Yoon et al, ; Zhang et al, ), and two have used only CT (Fu et al, ; Lins et al, ). These CT and CBCT studies reported a higher prevalence of BMC, in the range 0.05 to 69.0% (Table ).…”
Section: Bifid Mandibular Canalmentioning
confidence: 99%
See 2 more Smart Citations
“…CT and CBCT have been used to overcome the limitations of panoramic radiography (Fukami et al, ). So far, four studies have used both panoramic and CBCT (López‐Videla et al, ; Moro et al, ; Muinelo‐Lorenzo et al, ; Neves et al, ), two have used a combination of CT and CBCT (Rouas, Delbos, & Nancy, ; Shen et al, ), 21 have used only CBCT, one of them determining the prevalence of BMC in children (Afsa & Rahmati, ; Borgonovo et al, ; de Castro et al, ; de Oliveira‐Santos et al, ; Kang et al, ; Kuribayashi et al, ; Li et al, ; Luangchana et al, ; Naitoh et al, ; Neves et al, ; Ogawa et al, ; Okumu & Dumlu, ; Orhan et al, ; Orhan et al, ; Rashsuren et al, ; Shah et al, ; Sonneveld et al, ; Villa et al, ; Yang et al, ; Yi et al, ; Yoon et al, ; Zhang et al, ), and two have used only CT (Fu et al, ; Lins et al, ). These CT and CBCT studies reported a higher prevalence of BMC, in the range 0.05 to 69.0% (Table ).…”
Section: Bifid Mandibular Canalmentioning
confidence: 99%
“…There were similarities to the system of Langlais et al () but with the addition of buccal or lingual bifurcation, which could not have been identified by panoramic radiography. At least 12 teams of investigators (Kang et al, ; Li et al, ; López‐Videla et al, ; Muinelo‐Lorenzo et al, ; Okumu & Dumlu, ; Orhan et al, ; Orhan et al, ; Rashsuren et al, ; Sonneveld et al, ; Yang et al, ; Yi et al, ; Zhang et al, ) have used the Naitoh et al classification system to determine the prevalence of BMC in their respective populations. One of these groups concentrated their study only on children (Orhan et al, ).…”
Section: Bifid Mandibular Canalmentioning
confidence: 99%
See 1 more Smart Citation
“…e largest foramina are found in the retromolar area [2], and their corresponding canals are referred to as the retromolar canals (RCs). ese canals are sometimes considered as a type of bifid MC [3][4][5][6][7][8][9][10][11], but this assumption is not always true.…”
Section: Introductionmentioning
confidence: 99%
“…The articles that were included in the IAC/IANC group were excluded from this group. The most recent, consecutive 50 articles containing “mandibular canal” but neither “inferior alveolar canal” nor “inferior alveolar nerve canal” were included (defined as the MC group) (Abd Fattah, Hariri, Nambiar, Abu Bakar, & Abdul Rahman, 2019; Al‐Shayyab, Qabba'ah, Alsoleihat, & Baqain, 2019; Alves, Dias, Mansa, & Machado, 2020; Arias et al, 2019; Bosykh, Turkina, Franco, Franco, & Makeeva, 2019; Bozkurt & Görürgöz, 2019; Burian et al, 2019; Cârstocea, Săndulescu, Hostiuc, & Rusu, 2020; M. H. Chen et al, 2019; Costa et al, 2019; Esposito et al, 2019; Felice et al, 2019; Felice, Barausse, Pistilli, Ippolito, & Esposito, 2019; Fistarol, De Stavola, Fincato, & Bressan, 2019; Freire, Nascimento, Vasconcelos, Freitas, & Haiter‐Neto, 2019; Friedrich, Matschke, & Wilczak, 2019; Iwanaga et al, 2020, 2020; Iwanaga, Wong, Kikuta, & Tubbs, 2019; Kalabalik & Aytuğar, 2019; Koç, Eroğlu, & Bilgili, 2019; Komal, Bedi, Wadhwani, Aurora, & Chauhan, 2020; K. C. Lee, Yoon, Philipone, & Peters, 2019; Liye et al, 2019; Matsuda, Yoshimura, & Sano, 2019; Matzen, Petersen, Schropp, & Wenzel, 2019; Matzen, Villefrance, Nørholt, Bak, & Wenzel, 2020; Munhoz, Arita, Nishimura, & Watanabe, 2019; Na et al, 2019; Ngeow & Chai, 2020a, 2020b; Nicol, Loncle, Pasquet, & Vacher, 2019; Okumuş & Dumlu, 2019; Oliveira et al, 2019; Ozdede, 2020; Pedersen, Matzen, Hermann, & Nørholt, 2019; Predoiu, Rusu, & Chiriţă, 2019; Puciło, Lipski, Sroczyk‐Jaszczyńska, Puciło, & Nowicka, 2020; Raju et al, 2019; Sahl, Alqahtani, Alqahtani, & Gallez, 2018; Satir, 2019; Sholapurkar & Davies, 2019; Sinha et al, 2019; Sun et al, 2019; Tereshchuk & Sukharev, 2019; Uğur Ay...…”
Section: Methodsmentioning
confidence: 99%